In-Situ Study of Microstructure Evolution of Spinodal Decomposition in an Al-Rich High-Entropy Alloy - Jorgensen, Cameron S.; Santodonato, Louis J.; Littrell, Kenneth C.; Kuo, Chih Hsiang; Lee, Chanho; Unocic, Raymond R.; Liaw, Peter K.; Gilbert, Dustin A.; DeBeer-Schmitt, Lisa M. (Frontiers in Materials, 2022)
High-entropy alloys (HEAs) are known for their tendency to form single-phase solid solutions, especially at high temperatures. There is increasing recognition that HEAs, which undergo phase separation during cooling, may be well suited for functional applications such as memory storage and energy devices. This work presents a combined in-situ small angle neutron scattering (SANS) and scanning transmission electron microscopy (STEM) characterization study focusing on the microstructural evolution of Al1.3CoCrCuFeNi HEA as function of temperature. When exposed to temperatures up to 800 °C, the microstructure adiabatically disorders and abruptly homogenizing near 700 °C, which is consistent with spinodal decomposition. Overall, the microstructural evolution proceeds mainly by the atomistic redistribution of the constituent elements within simple crystal lattices, producing coherent phase mixtures.